A Aerobic Gymnastics in Warding Corona Covid-19 - Citra Azhariat Malasari (Lembaga Riset Ilmiah, 2022)
A strong immune system is one of the strongholds against the Covid-19 Corona virus. Regular exercise is a way to maintain health, fitness and endurance. UGM Sports Medicine Expert Zaenal Muttaqin Sofro said, there are many sports that can be done at home in the midst of the Corona pandemic. Maintaining a healthy physical condition is a very important thing to do during the Covid-19 pandemic. However, in the midst of a Covid-19 pandemic like this, physical activity and space are limited. How to work around this? Sports can be done with a homeworkout. It does not require excessive equipment, and can be accessed easily online such as aerobics. Aerobic exercise can be one of the sports to prevent the transmission of the Covid-19 virus. According to research results, people who regularly exercise are less likely to develop disease than people who rarely exercise. This is because when we exercise, the performance of white blood cells will be stimulated. These white blood cells that function as antibodies to fight various types of germs that enter the body. When exercising, body temperature also increases. This can inhibit bacteria from growing in the body, and the increased body temperature can also help the body fight infection.